Effect of a beta-cypermethrin and emamectin benzoate pesticide mixture on reproductive toxicity in male mice in a greenhouse environment. (12th February 2020) - Zhang, Yuanyuan; Kong, Chang; Chi, Huimin; Li, Junxia; Xing, Jie; Wang, Fei; Shao, Lijun; Zhai, Qingfeng
Abstract: With the widespread use of pesticides, the resistance to pesticides of pests has gradually increased, caused mixed pesticides to become even more widely used for practical applications. To investigate the effects of mixed pesticides on reproductive health in an occupational greenhouse environment, the greenhouse environment and the characteristics of the actual application were constructed, and then the male mice were comprehensively exposed to a mixture of the beta-cypermethrin and emamectin benzoate environmental. Additionally, the effect of the beta-cypermethrin and emamectin benzoate mixture on the reproductive health of male mice was known. The results showed that with the prolongation of exposure duration, the activities of Glutathione Peroxidase (GSH-Px), Total Superoxide Dismutase (T-SOD), Lactate dehydrogenase (LDH) and Acid phosphatase (ACP) in the testes of mice gradually decreased and the activity of Malondialdehyde (MDA) gradually increased. It was also found that the apoptosis rate of murine testicular cells increased and that DNA damage occurred with prolonged exposure duration. Therefore, it can be inferred that exposure to a mixture of the pesticides beta-cypermethrin and emamectin benzoate in the greenhouse environment may have adverse effects on the reproductive health of male mice.